2014
DOI: 10.3390/polym6123019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Thickness and Oxygen Transmission Rate before and after Thermoforming Mono- and Multi-layer Sheets into Trays with Variable Depth

Abstract: During thermoforming, plastic sheets are heated and subsequently deformed through the application of mechanical stretching and/or pressure. This process directly impacts sheet properties such as material thickness in walls, corners, and bottom, crystallinity in the constituent layers, and particularly the oxygen gas permeability. The aim of this study was to quantify the impact of thermoforming on thickness and oxygen transmission rate (OTR) of selected packaging materials (polypropylene (PP); PP/ethylene-viny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 30 publications
2
41
0
4
Order By: Relevance
“…Additionally the cooling step to prevent shrinkage after production and the cooling rate affect the crystallization of the polymer and therefore also the permeability. Buntinx et al (2014) also found that trays with straight corners performed better than round corners possibly due to the stretching of the EVOH. [39] 2.5.4.…”
Section: Thermoformingmentioning
confidence: 85%
See 2 more Smart Citations
“…Additionally the cooling step to prevent shrinkage after production and the cooling rate affect the crystallization of the polymer and therefore also the permeability. Buntinx et al (2014) also found that trays with straight corners performed better than round corners possibly due to the stretching of the EVOH. [39] 2.5.4.…”
Section: Thermoformingmentioning
confidence: 85%
“…Buntinx et al (2014) also found that trays with straight corners performed better than round corners possibly due to the stretching of the EVOH. [39] 2.5.4. Retort processing and similar treatments Careful attention needs to be paid when multilayer structures containing EVOH are exposed to a retort process (e.g., sterilization of ready meal and pet food).…”
Section: Thermoformingmentioning
confidence: 85%
See 1 more Smart Citation
“…Thermoforming imparts nonuniform deformation in the material which affects several properties such as mechanical strength, crystallinity of the constituent layers, thickness in corners, bottom and walls, and specifically gas transmission rates . There is a concern, particularly in the food packaging industry, whether the final formed product will maintain the barrier properties after the thermoforming process …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the samples need to be very carefully prepared and sealed to avoid leakage problems during testing. There is a strong interest to estimate oxygen transmission rate (OTR) in the package based on the OTR and thickness of the unconverted film or sheet …”
Section: Introductionmentioning
confidence: 99%